Funerary monuments in the main church in Breda, a critical restoration history (Bulletin KNOB, 2010)
The main church in Breda contains a number of top-quality funerary monuments dating from the late Gothic and Renaissance period, which are connected with the Dutch royal family Oranje-Nassau. They were preserved relatively intact, but restored with rather varying success. In retrospect, one is struck by the extent to which the views on restoration changed in through the centuries. Whereas in 1828 modest addition and repair (although in a deviating material like marble) were still opted for, in 1860 a historicizing reconstruction was aimed at, which was even partly made subordinate to the ideological-religious views of the restorers and their adviser. The underlying idea of the restoration of 1951 was more reserved and particularly directed at restoration of the severely impaired construction, without violating the authenticity too much.Replacement of components primarily took place in this restoration philosophy. The more recent activities appear to have been motivated chiefly by a need for rubbing off damage and a strong fear of rusty dowels. However, this fear appeared to be used as a licence for interventions in the (historically grown) authenticity of monuments, which according to modern restoration ethics are acceptable only very rarely and after careful preliminary research. The restoration of sculptural ensembles was too much considered a secondary part of architectural restoration, whereas in such high-quality and significant examples of sculpture an isolated tailor-made approach by specialists is an absolute requirement.A very careful and reserved policy of conservation (and preferably not restoration) is suitable here, according to methods that have been generally accepted in the museum world for a long time. However, since in the world of building-restoration dismantling as a method is absolutely customary and accepted, there is frequently less hesitation also to proceed to such a rigorous intervention when it concerns vulnerable and refined sculptural ensembles.The unusually pure condition of most Breda monuments creates large obligations for the custodians of the church. The damage caused by the 16th-century iconoclasts and by patriots in the late eighteenth century gave the Breda monuments an extra historical dimension, besides the high artistic and art-historical qualities of this funerary ensemble. Hardly anywhere can one see so clearly how systematically iconoclasm caused havoc in the Netherlands. Consequently, any intervention in these funerary monuments is actually one too much. Unfortunately, here too, it is rather difficult to curb the passion for restoration and the urge to polish still dominating in the Netherlands. This requires a change in mentality which is hard to realize: commissioners experience damage and signs of wear and tear as disturbing; moreover, restorers have a certain professional interest in decline – just as doctors have in diseases, although naturally this is never mentioned aloud.